2007
DOI: 10.1159/000103303
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Chorionic Villus Sampling in the Presence of Asymptomatic Subchorionic Hematoma

Abstract: Objective: According to our knowledge the safety of chorionic villus sampling (CVS) has not been studied in the presence of subchorionic hematoma (SCH). Our study aimed to evaluate the effects of CVS on the procedure-related fetal loss rate in patients with SCH. Method: Fifty-six patients with asymptomatic SCH (cases) and 986 controls in whom there was no hematoma underwent elective CVS for a prenatal diagnosis of β-thalassemia and were entered into a prospective study. Mean gestational age (±SD) at diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…There are many studies in the literature investigating the rela tionship between SHC and abortion. Although some of them re ported that they increased the abortion rate [4,[10][11][12], the num ber of studies reporting that they did not increase the abortion rate is also substantial [5,6]. Zhou et al reported that the rate of low birth weight increased but the rate of abortion did not increase in pregnant women with SCH in their study evaluating 1,097 preg nant women [6].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many studies in the literature investigating the rela tionship between SHC and abortion. Although some of them re ported that they increased the abortion rate [4,[10][11][12], the num ber of studies reporting that they did not increase the abortion rate is also substantial [5,6]. Zhou et al reported that the rate of low birth weight increased but the rate of abortion did not increase in pregnant women with SCH in their study evaluating 1,097 preg nant women [6].…”
Section: Discussionmentioning
confidence: 99%
“…The most feared situation in a patient with a SCH is pregnancy loss. Although a large systematic review showed that SCH was correlated with a twofold increase in spontaneous abortion 4 , other studies found no association between SCH and pregnancy loss 5 6 . The aim of this study is to investigate the relationship between first trimester SCH and pregnancy loss in women with singleton pregnancies.…”
Section: Introductionmentioning
confidence: 98%
“…The impact of SCH on early pregnancies has been disputed; prior studies in the fertile population have shown increased rates of pregnancy loss, 4 , 5 , 6 while recent studies demonstrate no increased risk. 1 , 7 Few studies have evaluated SCH among the infertile population, and these have focused primarily on pregnancies conceived by in vitro fertilization (IVF). Additionally, the majority of these studies have focused on identifying risk factors for SCH and not on evaluating the impact of SCH on pregnancy outcomes such as first trimester loss or live birth rate.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of SCH on early pregnancies has been disputed; prior studies in the fertile population have shown increased rates of pregnancy loss, 4–6 while recent studies demonstrate no increased risk 1,7 . Few studies have evaluated SCH among the infertile population, and these have focused primarily on pregnancies conceived by in vitro fertilization (IVF).…”
Section: Introductionmentioning
confidence: 99%
“…The clinical signi cance of SCH in early pregnancy remains controversial, and whether it increases the risk of adverse pregnancy outcomes is still uncertain. Some studies reported that SCH increased the risk of miscarriage [5,6], while others reported null associations [7,8]. Increased risks of fetal growth restriction and preterm delivery associated with SCH were also reported in some but not all studies [9,10].…”
Section: Introductionmentioning
confidence: 99%